"FEApps": Boosting students' enthusiasm for coding and app designing, with a deeper learning experience in engineering fundamentals. Issue 3 (2nd March 2016) - Bishay, Peter L.
ABSTRACT: In this article, a model for a multi‐goal course project is reported and discussed. Teams of students are asked to create attractive Matlab Apps for topics related to "Fundamentals of Engineering" (FE) exam (hence called "FEApps"). The main goals of this project, discussed in details in the article, are: (1) allowing students practice coding in a new innovative environment, (2) encouraging students to think as designers who create user‐friendly and robust products or services and their user manuals, (3) giving students the chance to work in teams with more useful interactions among teams, (4) showing students the benefit of writing multiple drafts for their projects and getting many feedback before the final presentations, and (5) refreshing students' knowledge about topics related to FE exam. The article provides some examples of "FEApps" created by the participating students. This course project guarantees the highest student retention rates based on the well‐known "learning pyramid" and focuses on one of the relatively difficult mechanical engineering program outcomes, specified by the ABET, which is outcome i: "a recognition of the need for, and an ability to engage in life‐long learning." The project assessment survey results proved that all project goals had been successfully met. © 2016 Wiley Periodicals, Inc. Comput Appl Eng Educ 24:456–463, 2016; View this article online atwileyonlinelibrary.com/journal/cae ; DOI10.1002/cae.21723